MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN DISCOVERY LEARNING MATERI HIMPUNAN - Fadly Samsudin; Masta Hutajulu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research was conducted at SMP Pembangunan 1 Baleendah students of class VII researchers using the discovery learning model aimed at improving students' learning outcomes in set materials. The type of research used class action research conducted in the II cycle method used is descriptive qualitative. The material used in the form of , in this class action research researcher only focuses on student learning outcomes because the lack of learning outcomes affects the learning process therefore researchers use II, aiming to see results before and after being given video or ICT assistance with discovery learning. In cycle I class action research students gain small grades and understand the material due to too long online learning makes students become lazy in learning, cycle II experiencing an increase in learning outcomes by using the help of video or ICT students eagerly back in learning. Thus, the study of class actions conducted in Junior High School Development Works 1 Baleendah class VII students using the discovery learning learning model is divided into II cycles with the help of providing video in the form of set summary material resulting in changes in student learning outcomes for the better, therefore the provision of video or ict affects learning outcomes.